2023
DOI: 10.1038/s41420-023-01506-x
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of FKBP5 protects β-cell survival under inflammation stress via AKT/FOXO1 signaling

Abstract: The FK506-binding protein 51 (FKBP51, encoded by FKBP5 gene) has emerged as a critical regulator of mammalian endocrine stress responses and as a potential pharmacological target for metabolic disorders, including type 2 diabetes (T2D). However, in β cells, which secrete the only glucose-lowering hormone—insulin, the expression and function of FKBP5 has not been documented. Here, using human pancreatic tissue and primary human islets, we demonstrated the abundant expression of FKBP5 in β cells, which displayed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Our study also identified several pairs of DE miRNAs and their target mRNAs which linked to the regulation of β-cell mass. Specifically, the FK506-binding protein 51 (encoded by FKBP5 gene) emerged as a crucial regulator for T2DM, with its inhibition known to protect β-cell survival via AKT/FOXO1 signaling [ 39 ]. Our results revealed that FKBP5 was downregulated in HFD mice compared with CD group, indicating a pro-survival mechanism mediated by inhibition of FKBP5 against inflammatory stress in T2DM.…”
Section: Resultsmentioning
confidence: 99%
“…Our study also identified several pairs of DE miRNAs and their target mRNAs which linked to the regulation of β-cell mass. Specifically, the FK506-binding protein 51 (encoded by FKBP5 gene) emerged as a crucial regulator for T2DM, with its inhibition known to protect β-cell survival via AKT/FOXO1 signaling [ 39 ]. Our results revealed that FKBP5 was downregulated in HFD mice compared with CD group, indicating a pro-survival mechanism mediated by inhibition of FKBP5 against inflammatory stress in T2DM.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, a negative correlation between miR-100-5p levels and FKBP5 levels was detected for the first time, and a luciferase reporter confirmed the presence of RNA interactions. FKBP5 belongs to a class of immunophilin proteins and is involved mainly in protein folding, protein transport, and immune regulation 42 , 43 . Some reports have also revealed a role for FKBP5 in promoting apoptosis and autophagy 44 .…”
Section: Discussionmentioning
confidence: 99%
“…All samples were assayed in triplicate, and the values were normalized to GAPDH. The quantitative mRNA was normalized by using the 2 -ΔΔCt method 29 .…”
Section: Real-time Quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%